(untitled) (Minerva, 2019)
The current interpretation of the Old Persian Infinitives in <-ta-na-i-ya> as /-tanai/ is not the only possible one. Since in the Old Persian writing system there is no sign and consequently the possibility of a spelling † <-ta-ni-i-ya> is excluded, <-ta-na-i-ya> can also conceal /-tani/, i.e. a «locative» infinite. A study of the Old Persian data and the evidence for the morphosyntax of the infinitive formations in the Indo-Iranian languages (especially Ved. puputáni and some isolated formations in -(C)ani; Late Av. (o) dataniia-, Ved. -ténya- as derivatives of an Indo-Iran. Inf. *-tani and the possibility of a Indo-Iranian System with *(C)ai and *-(C)ani Forms (*-Ø-ai : *-(e)s-ai : *-u-ai : *-t-ai : *– Ø-ani : *-s-an-i : *-uan-i : *-tan-i) lends support to the interpretation of OP <-ta-na-i-ya> as /-tani/ and makes it at least as plausible as the current one.